2(x+4)+2=8x+2(x+2)

Simple and best practice solution for 2(x+4)+2=8x+2(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+4)+2=8x+2(x+2) equation:


Simplifying
2(x + 4) + 2 = 8x + 2(x + 2)

Reorder the terms:
2(4 + x) + 2 = 8x + 2(x + 2)
(4 * 2 + x * 2) + 2 = 8x + 2(x + 2)
(8 + 2x) + 2 = 8x + 2(x + 2)

Reorder the terms:
8 + 2 + 2x = 8x + 2(x + 2)

Combine like terms: 8 + 2 = 10
10 + 2x = 8x + 2(x + 2)

Reorder the terms:
10 + 2x = 8x + 2(2 + x)
10 + 2x = 8x + (2 * 2 + x * 2)
10 + 2x = 8x + (4 + 2x)

Reorder the terms:
10 + 2x = 4 + 8x + 2x

Combine like terms: 8x + 2x = 10x
10 + 2x = 4 + 10x

Solving
10 + 2x = 4 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
10 + 2x + -10x = 4 + 10x + -10x

Combine like terms: 2x + -10x = -8x
10 + -8x = 4 + 10x + -10x

Combine like terms: 10x + -10x = 0
10 + -8x = 4 + 0
10 + -8x = 4

Add '-10' to each side of the equation.
10 + -10 + -8x = 4 + -10

Combine like terms: 10 + -10 = 0
0 + -8x = 4 + -10
-8x = 4 + -10

Combine like terms: 4 + -10 = -6
-8x = -6

Divide each side by '-8'.
x = 0.75

Simplifying
x = 0.75

See similar equations:

| (7x+84)=112 | | 3x+2x-2=4x+x+2 | | -0.2-q=9q | | X*.05833333333=(X-113) | | N^7/10 | | 2g+3G=10 | | 4(-y+2)=-1 | | X/3=70 | | N^10/7 | | 2m+-3m-8=26 | | Px+Q=X+1 | | 2x+4(2x+8)=10x+32 | | 1+8x^2+x^4= | | 90=(4x+12)+(6x+8) | | 4In(2x+3)=11 | | .15x+x=97.75 | | 4m+m=-90 | | (x+12)(x-7)=0 | | [8x]=28 | | .25(x+4)=41 | | 7/6=x/5 | | (7/28)=(3/x) | | 3x+24=4-10 | | 3(a+1)=5(a-1) | | x^3-2x^2-09+18=0 | | -112/16 | | 5x(3x-5)(x+1)=0 | | y=e^2x+17 | | Y=2x+a | | (9a-3)/3 | | Bj+m=j | | 16[x-3]=-80 |

Equations solver categories